Stapled Hemorrhoidectomy in Third Degree Hemorrhoids: A Prospective Study - Bashir Ahmed Shaikh; Asma Niaz Khan; Foad Moosa; Naheed Sultana (Journal of the Dow University of Health Sciences, 2011)
Objective: To study the outcome of Stapled haemorrhoidectomy in 3rd degree hemorrhoids. Materials & Methods: 50 patients, who underwent stapled hemorrhoidectomy, were included in this study. The study took place at Surgical Unit-I, Civil Hospital, Karachi, from January 2009 to December 2010. Design: Prospective interventional study. Results: Stapled hemorrhoidectomy (SH) was performed in 3rd degree haemorrhoidsÂ  in 50 patients. 3 patients had minimum pain and only 1 patient had persistent pain and one patient had post-operative minor bleeding which was managed conservatively. Conclusion: SH is an effective surgical procedure for the treatment of 3rd degree haemorrhoids. There is strong evidence that SH results in less postoperative pain than other procedures as well as earlier mobility. In our experience, SH is the treatment of choice for third degree hemorrhoids in hospitalized patients